Adaptabilité Biologique Chez Des Enfants Issus De Milieu De Vie Différent - Kouadio Kouakou Jérôme; Kouassi Kouakou Firmin; Kouamé N’guessan Pazé (European Scientific Journal, ESJ, 2018)
The biological adaptability of the child seems to be realized according to the living conditions that are offered to him. The influence of these conditions on the biophysiological functioning of the child was not sufficiently examined. This paper focuses on comparing the biological adaptability of children living in poorer socio-health conditions to that of their peers from a more appropriate socio-health environment. It covered 189 Ivorian children aged between 6 and 59 months, including 103 from inadequate social and health care settings and 86 that was selected in a relatively adequate sociohealth environment. The examination of the biological adaptability of the two groups of children was done by considering the frequencies of physical diseases. The results show that infants and children who live in an environment that lacks infrastructure for quality drinking water, hygienic toilet for their needs, lost wells or washbasins for sewage disposal, and trashes or covered barrels for the conservation of household garbage have a higher rate of biological miss-adaptabilities than their peers from an environment that offers these possibilities. The rate of malaria (26.4%, 20.6%), intestinal infections (28.4%, 37.4%), anemia (7.5%, 10.9%) in infants and children whose health and social needs are not realized differ significantly from those of their counterparts who have less difficulty achieving theirs (malaria: 19.5%, 18.4%, intestinal infections: 0%, 0%, anemias: 0%, 0%). These results confirm the hypothesis that the structuring of the living environment is a factor that has a variable effect on biological adaptability.